Problems and Needs in English Language Teaching from the Viewpoints of Pre-service English Teachers in Thailand - Oeamoum, Nutcha; Sriwichai, Chuanpit (Asian Journal of Education and Training, 2020)
This study aimed to explore the problems and needs in English language teaching (ELT) of pre-service English teachers in Thailand related to three aspects 1) curriculum and content, 2) instructional materials, and 3) teaching methods. The participants were thirty fourth-year pre-service English teachers from five universities located in Northern, Central, Northeastern, and Eastern Thailand. The findings from questionnaire and semi-structure interview revealed that the problems and needs in ELT related to curriculum and content were insufficient number of study hours of each English course, inadequate courses for specific English skills, outdated curriculum, and inapplicable content to the real life. Therefore, the participants needed the curriculum focusing on real-world context and communication skills (e.g. speaking and listening skills). The main problems related to instructional materials were non-diverse, insufficient, and ineffective teaching aids, so the participants required teachers to use diverse instructional materials and integrated web-based technology in English classes. Finally, the major problems and needs related to teaching methods included lack of specialists in teaching specific courses and uninteresting teaching technique focusing on lecturing grammar rules and reading rather than practicing communication skills; hence, the pre-service English teachers mainly expressed the needs to learn using games, role play, and oral presentation as these methods were interesting and could increase opportunities to produce target language.